2015
DOI: 10.3390/ijerph121013224
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Mother-To-Child Transmission of HIV Infection: The Drug Resource Enhancement against AIDS and Malnutrition Model

Abstract: The Drug Resource Enhancement against AIDS and Malnutrition Program (DREAM) gathered professionals in the field of Elimination of HIV-Mother-To-Child Transmission (EMTCT) in Maputo in 2013 to discuss obstacles and solutions for the elimination of HIV vertical transmission in sub-Saharan Africa. During this workshop, the benefits of administrating combined antiretroviral therapy (cART) to HIV positive women from pregnancy throughout breastfeeding were reviewed. cART is capable of reducing vertical transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…The present study did not allow identification of risk factors [14][15][16][17] This demonstrates the importance of early diagnosis and subsequent treatment in order to reduce the risk factors for vertical transmission.…”
Section: -13mentioning
confidence: 81%
See 1 more Smart Citation
“…The present study did not allow identification of risk factors [14][15][16][17] This demonstrates the importance of early diagnosis and subsequent treatment in order to reduce the risk factors for vertical transmission.…”
Section: -13mentioning
confidence: 81%
“…One factor that helps reduce the possibility of vertical transmission is the use of medication to inhibit lactation, and 95.9% of the pregnant women in this study were found to be using this medication. 4,8,12,[14][15][16][17][18] Use of antiretroviral drugs during pregnancy increases the The cases of 81.1% of the HIV-positive pregnant women were only notified in the third trimester, thus indicating that there were delays in notification. In Brazil, notification is supposed to occur at the time of detection of HIV infection in pregnant women and/ or children infected by vertical transmission.…”
Section: -13mentioning
confidence: 99%
“…Em estudo realizado em hospital sul africano revelou a previdência de doenças como a pneumonia e infecção do trato urinário associados ao HIV, em crianças que necessitaram internação hospitalar (4) . Pesquisa realizada com crianças de Malawi na África demonstrou as múltiplas internações em pacientes com menos de dois anos, essa alta demanda de internações sugere a necessidade de melhoria contínua do diagnóstico precoce (8) .…”
Section: Discussionunclassified
“…Em contextos de recursos limitados, metade das crianças que contraem o HIV de suas mães morre, com destaque para a vulnerabilidade à HIV/AIDS em crianças entre zero a 12 anos e os adolescentes de 13 a 19 anos. No entanto, essas mortes são evitáveis com o diagnóstico precoce, acompanhado de tratamento antirretroviral e profilaxia de infecções oportunistas (4) .…”
Section: Introductionunclassified
“…Other efforts are focused on the invention of antiviral medications effective against the Zika virus. In HIV/AIDS and syphilis, in utero infections are almost completely controlled by effective chemotherapy . We can expect new antiviral medicines to control ZVI in utero.…”
Section: Discussionmentioning
confidence: 99%